Alkaloids from roots of Alseodaphne corneri Kosterm - Nafiah, Mohd Azlan; Mukhtar, Mat Ropi; Morita, Hiroshi; Ahmad, Kartini; Awang, Khalijah; A. Hadi., Hamid (Malaysian Journal of Science, 2010)
This is the first report on the occurrence of bisbenzylisoquinoline alkaloids in Alseodaphne corneri which belongs to the family of Lauraceae. Chemical studies on the roots of this species have yielded four bisbenzylisoquinoline alkaloids; (-)-gyrolidine 1, norstephasubine 2, (+)-2-norlimacusine 3 and (+)-stephasubine 4. The isolation was achieved by chromatographic techniques and the structural elucidation was performed via spectral methods; namely ID and 2D NMR, IR, UV and MS, and in comparison with published literature.